Initial Development of a Voice-Activated Astronaut Assistant for Procedural Tasks: From Need to Concept to Prototype - Aist, Gregory; Bohus, Dan; Boven, Brad; Campana, Ellen; Early, Susana; Phan, Steven (Interactive Instruction Development, 2004)
We began with an idea: existing spoken interface technology might help astronauts preparing to work aboard the International Space Station (ISS). Over three years, the project evolved into a prototype system useful not only for training, but also for guiding astronauts through procedures while aboard the ISS. This paper describes our journey from a vague idea that “technology could help” to a working prototype that has support from many levels within NASA. Factors of our success included repeated meetings between developers and end-users, and providing working prototypes at each stage.